REPRESENTASI NILAI KARAKTER FILM SUSI SUSANTI SEBAGAI RELEVANSI BAHAN AJAR TEKS BIOGRAFI DI SEKOLAH MENENGAH ATAS - Ryana Anggita Shandi, - (2022)
The biographical story is one of the stories of famous figures whose lives are worthy of imitation. Nowadays, a biography can be poured through Films, one of which is Susi Susanti's Film. The purpose of this study is to describe the character values of Susi Susanti's character and use it as teaching material in learning biographical texts. The research method used is descriptive qualitative. Data collection techniques are literature study and documentation. Based on the results of the research conducted, it was found that there are 5 character values that stand out from Susi's character, namely religious values, courage, curiosity, struggle, and perseverance. In addition, the structure found in the biographical Film is the existence of facts and story tools that highlight the background and plot elements that support the movement of Susi's life and the involvement of other characters. These values are analyzed using Roland Barthes' semiotic theory and Robert Stanton's structural theory. After that, the results of the analysis are used as a reference in designing teaching materials that are used in learning biographical texts on the basic competencies of 3.14 and 4.14 of the 2013 curriculum.